Estuarine Suspended Sediment Dynamics: Observations Derived from over a Decade of Satellite Data - Reisinger, Anthony; Gibeaut, James C.; Tissot, Phillippe E. (Frontiers in Marine Science, 2017)
Suspended sediment dynamics of Corpus Christi Bay, Texas, USA, a shallow-water wind-driven estuary, were investigated by combining field and satellite measurements of total suspended solids (TSS). An algorithm was developed to transform 500-meter Moderate Resolution Imaging Spectroradiometer (MODIS) Aqua satellite reflectance data into estimated TSS values. The algorithm was developed using a reflectance ratio regression of MODIS Band 1 (red) and Band 3 (green) with TSS measurements (n=54) collected by the Texas Commission on Environmental Quality for Corpus Christi Bay and other Texas estuaries. The algorithm was validated by independently collected TSS measurements during the period of 2011-2014 with an uncertainty estimate of 13%. The algorithm was applied to the period of 2002-2014 to create a synoptic time series of TSS for Corpus Christi Bay. Potential drivers of long-term variability in suspended sediment were investigated. Median and IQR composites of suspended sediments were generated for seasonal wind regimes. From this analysis it was determined that long-term, spatial patterns of suspended sediment in the estuary are related to wind-wave resuspension during the predominant northerly and prevalent southeasterly seasonal wind regimes. The impact of dredging is also apparent in long-term patterns of Corpus Christi Bay as concentrations of suspended sediments over dredge spoil disposal sites are higher and more variable than surrounding areas, which is most likely due to their less consolidated sediments and shallower depths requiring less wave energy for sediment resuspension. This study highlights the advantage of how long-synoptic time series of TSS can be used to elucidate the major drivers of suspended sediments in estuaries.